Gender wage discrimination in Brazil from 1996 to 2015: A matching analysis - Thiago Fonseca Morello; Jacqueline Anjolim (EconomiA, 2021)
The discriminatory component of the gender wage gap was found to be significant and to decrease over time by previous studies, most of them based on the Oaxaca-Blinder decomposition (OBD). Such evidence is disputable for being grounded on the assumption of full common support between men and women, which has been increasingly refuted by international literature. Seeking to fill this gap for the case of Brazil, the paper revisits household survey data from 1996 to 2015 with propensity score (PS) and nearest-neighbour (NN) matching techniques. As results, the discriminatory component was confirmed to be significant in all years and not to follow a systematic decaying trend across the years - the fall observed from 1996 to 2004 was offset in 65% by a subsequent increase. Gender discrimination was heterogeneous throughout occupational categories, being especially high in management positions. Estimates, albeit belonging to the range of previous studies, also challenged the gap closing trend suggested by these studies. Given ongoing recession and high informality, it is uncertain whether further progress towards gender wage equality in Brazil will emerge spontaneously from the private sector or whether specific policy is needed.
Keywords: J16; J71; C21; 330; Gender wage gap; Matching; Propensity score